The rhyme of Grygoriy Skovoroda as a language phenomenon - Dyadyshcheva-Rosovetska, Juliya (Current issues of Ukrainian linguistics: theory and practice, 2019)
Specific language of the Gregory Skovoroda still attract the attention of scientists, especially common are discussions on combination of elements of the different origin in his poetics. The emphasis is on the method of reconstruction of features of the language of ancient texts, which is a complex set of procedures. The various approaches of scientists to the linguistic interpretation of Skovoroda’s texts are analyzed: certain heterogeneity taking into account stylistic differentiation, approaching to Russian, a mixture of Church Slavicisms, Ukrainianisms, Russisms, pseudo-Ukrainianisms and pseudorussisms, a combination of the traditional Old Slavonic element with the linguistic folk, the Slavic Ukrainian book 2 half of the XVIII century Etc., a qualitatively new phenomenon, representing the only Eastern Slavic literary language. Unfortunately, the problem of language of the Gregory Skovoroda is usually observed only from the point of view of the current state of development of the Ukrainian language and the processes that occur in it at the beginning of the XXI century. This study’s autor approaches this issue from diachronic point of view, reconstructing G. Skovoroda’s speech issues in the context of the language environment of his time and using a comparative method to identify the original pronunciation of the G. Skovoroda’s the poetry in relation to the spelling of his poetic texts. With this instrumentary, rhyme in a number of poems becomes available to study. In particular, proposed method is used upon a "Tenth song" from the series "Garden of Divine Songs", only its author’s version on autograph rough copy becouse versions published in academic collections in 1973 and 2011 hold traces of adaptation to the norms of modern spelling. Based on our observations on the draft of the autograph’s Song "To Every City Its Customs and Laws" by G. Skovoroda, we can conclude that when reading the poetry of the G. Skovoroda using Ukrainian language phonetic signs, rhyme is accurate, whereas in rules of "Russian" reading - is inaccurate. This is the evidence for the important role of the Ukrainian component in the language of the poet-philosopher and that his poems are ment to be read using ukrainian rules. In the perspective, proposed approach can be applyed to analyze the language of other poetic works by Gregory Skovoroda.